La misma luna : [videorecording (DVD)] = Under the same moon - Riggen, Patricia; Castillo, Kate del, 1972-; Derbez, Eugenio; Alonso, Adrián, 1994- (20th Century Fox Home Entertainment, 2008)
Tells the parallel stories of nine-year-old Carlitos and his mother, Rosario. In the hopes of providing a better life for her son, Rosario works illegally in the U.S. In Mexico, her mother cares for Carlitos. Unexpected circumstances drive both Rosario and Carlitos to embark on their own journeys in a desperate attempt to reunite. Along the way, mother and son face challenges and obstacles but never lose hope that they will one day be together again.